The Estimation of relationship between actuarial rate of return, Maturity and Coupon: The case of Tunisia - Elmguirhi, Sonia (Operations Research: International Conference Series, 2024)
The aim of this paper is to study the Estimation of the relationship between the actuarial rate of return, Maturity and Coupon issued by the Tunisian banking and financial institutions knowing that it is a significant component of financing. So, this relationship issue is an essential link of investments. The studying of yield bond is an important first step. For many types of financial research. To  date, this research has focused on the bond yield for institutions, with the exception of works by institution, financial and banking. There regression models are tested by different methods. The first model is based only on relationship between Actuarial Rate of Return, maturity and coupon. The other models are prominent in the published literature on the bond yield.